2016
DOI: 10.1016/j.jpainsymman.2016.03.020
|View full text |Cite|
|
Sign up to set email alerts
|

Anticholinergic Drug Burden in Noncancer Versus Cancer Patients Near the End of Life

Abstract: Context Anticholinergic drugs can cause several side effects, impairing cognition and quality of life (QOL). Cancer patients are often exposed to increasing cumulative anticholinergic load (ACL) as they approach death, but this burden has not been examined in patients with non-malignant diseases. Objectives To determine ACL and its impact in non-cancer versus cancer palliative care patients. Methods We performed a secondary analysis of 244 subjects enrolled in a randomized controlled trial. ACL was quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Furthermore, the majority of older people are exposed to drugs with anticholinergic and/or sedative effects ( 49 ), and resorting to anticholinergics and sedatives to control pain, dyspnea, secretions and patient anxiety, among other symptoms, is common in palliative care ( 50 ). Thus, in our study, most of the anticholinergic and/or sedative drugs prescribed at the EOL are related to drugs for symptomatic use, and their use increased as the patient approached the EOL, which is consistent with previous studies ( 51 , 52 ). This could be due to the increase of DBI during patient follow-up, which could be related to an increase in psychotropic medications for symptom management at EOL.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the majority of older people are exposed to drugs with anticholinergic and/or sedative effects ( 49 ), and resorting to anticholinergics and sedatives to control pain, dyspnea, secretions and patient anxiety, among other symptoms, is common in palliative care ( 50 ). Thus, in our study, most of the anticholinergic and/or sedative drugs prescribed at the EOL are related to drugs for symptomatic use, and their use increased as the patient approached the EOL, which is consistent with previous studies ( 51 , 52 ). This could be due to the increase of DBI during patient follow-up, which could be related to an increase in psychotropic medications for symptom management at EOL.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the comparative analysis of the baseline pharmacotherapeutic characteristics between different degrees of frailty highlighted a higher DBI in those with advanced frailty. This may be related to a situation closer to the EOL, which requires these patients to use more drugs with anticholinergic and sedative characteristics [ 33 , 34 , 35 ]. Notably, greater exposure to drugs with anticholinergic activity is associated with more fatigue, dry mouth, worse concentration, and worsening status at EOL [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Despite documented risks and AGS recommendations, the use of medications with anticholinergic properties remains prevalent in older adults with dementia and in patients near the EOL. 8,11,12 A retrospective study evaluating anticholinergic drug use in over 89 000 patients and its impact on cognitive function found that mean Anticholinergic Cognitive Burden (ACB) scores were highest in patients with dementia. 13 In a similar retrospective analysis of Medicare data, it was found that 77% of nursing home residents with dementia used at least 1 DAP each month and of those residents, 34% used DAPs with an ACB scale of 2 or 3.…”
Section: Introductionmentioning
confidence: 99%